Critical factors in fatal collisions of adult cyclists with automobiles - Bíl, Michal; Bílová, Martina; Müller, Ivo (Accident; analysis and prevention, 2010)
This article evaluates, by means of multivariate regression, critical factors influencing the collisions of motor vehicles with adult (over 17 years) cyclists that result in fatal injury of cyclists. The analysis is based on the database of the Traffic Police of Czech Republic from the time period 1995-2007. The results suggest that the most consequential categories of factors under study are: inappropriate driving speed of automobile; the head-on crash; and night-time traffic in places without streetlights. The cyclists' faults are of most serious consequence on crossroads when cyclists deny the right of way. Males are more likely to suffer a fatal injury due to a collision with a car than females. The most vulnerable age group are cyclists above 65 years. A fatal injury of a cyclist is more often driver's fault than cyclist's (598 vs. 370). In order to reduce the fatal risk, it is recommended to separate the road traffic of motor vehicles from bicyclists in critical road-sections; or, at least, to reduce speed limits there.
Keywords: dospělí; Female; Safety; multivariační analýza; Cause of Death; Adult; Automobiles; ženské pohlaví; mladý dospělý; Accidents, Traffic; Multivariate Analysis; Adolescent; lidé; Environment Design; automobily; Bicycling; právní odpovědnost; Risk Factors; Acceleration; cyklistika; Male; Aged; Young Adult; životní prostředí - projekt; Athletic Injuries; Liability, Legal; rizikové faktory; bezpečnost; sportovní úrazy; lidé středního věku; zrychlení; senioři; mužské pohlaví; příčina smrti; Middle Aged; mladiství; dopravní nehody; Humans